Korelasi Nilai CBR Laboratorium dan DCP terhadap kondisi Proyek Pembangunan Jalan Tepus – Jerukwudel II - Riandana Rizky Praja; Budi Priyanto (Politeknik Negeri FakFak, 2022)
Soil in a construction must have a high soil density value, a high soil density value affects the carrying capacity of the soil in carrying the load on it. dynamic cone penetration test / DCP (Dynamic Cone Penetrometer) is often performed. To get the CBR value, the DCP test results are correlated with a DCP-CBR Value Correlation formula. However, to anticipate deficiencies in the CBR-DCP correlation test, it is necessary to correct it with the DCP-CBR Correlation Formula from the Ministry of Public Works and Housing which is generally accepted for all regions of Indonesia. This research was conducted by conducting DCP tests at 8 points in the field and then taking soil samples which would then be taken to the laboratory to test the physical properties of the soil. After all the data has been obtained, then analyze and formulate the DCP – CBR correlation formula and compare it with the correlation formula. After doing the research, it is found that the DCP – CBR correlation formula model studied has the formula Log CBR = 3.2322 – 1.512 Log DCP, where this formula is generally in accordance with the DCP – CBR correlation formula from the Ministry of Public Works because of the position of the curve. slightly above the curve of the DCP-CBR Correlation formula of the Ministry of PUPR